Gossypol Effect in Some blood parameters, enzymes and pathology of male common carp Cyprinus carpio l. - Al-Tayyar, Omar B.A.; A. Al-Beiati , Muhannad; A.Al-Ubade, Sana (The Iraqi Journal of Veterinary Medicine, 2009)
Gossypol is a substance found in the cottonseed. Recently in Iraq and in other countries the cottonseedwas used as a concentrate for fish and other animals without awareness of the risk. The present study isdesigned to shed the light on the deleterious effect of gossypol on some hematological parameters andenzymes of male common carp Cyprinus carpio l.. Oral administration of gossypol 20 mg./kg. b.w. forten days was found to be a strong lyses for red blood cell, reduced packed cell volume and increasederythrocyte sedimentation rate and decreased total white blood cell. Furthermore alkalinephosphotase, alinine aminotransferase and aspartate aminotransferase were increased which reflectliver and kidneys damage caused by gossypol coincided with the histopathological changes in whichthere was mainly degeneration as well as inflammatory cells infiltration